A FUZZY MULTI-CRITERIA DECISION APPROACH FOR MEASURING TECHNOLOGY COMPETENCY PERFORMANCE OF SMEs - Bolukbas, Ufuk; Guneri, Ali Fuat (YILDIZ TECHNICAL UNIV, 2017)
This paper researches on the technology competency, management capability and firm performance. Technology competency and strategic management becomes more and more important for enterprises to keep their competitive power in the sector. Technology and management competency determines capabilities of enterprises to compete in the sector and has a critical importance for the innovative researches and development. The development of the research model is based on the empirical studies of the management from technology literature. Data were collected from a sample of 450 Turkish manufacturing firms which was obtained by stratified sampling from the registered firm database of Istanbul Chamber of Industry. A hierarchical performance evaluation model is structured based on the six main competency dimensions that are determined by expert evaluation and based on the literature review. In this study, a fuzzy multi-criteria decision making approach is proposed to evaluate technology competency performance of the manufacturing firms in Istanbul, Turkey. Small and medium-sized enterprises (SMEs) are analyzed and evaluated with respect to technology survey responses in which processes management, products, information and communication technology, marketing strategy, innovation and entrepreneurial activities and research and developments (R&D) issues are investigated. Fuzzy analytic hierarchy process (FAHP) method is used to determine the weights of the decision criteria. These criteria weights and responses of survey analysis (data) related with the enterprises are input for the VIKOR method to rank the firms.
Keywords: Technology competency; multi criteria decision making (MCDM); small and medium-sized enterprises (SMEs); MAKING METHODS; AHP; Engineering